Pathophysiological Underpinnings of Extra-Motor Neurodegeneration in Amyotrophic Lateral Sclerosis: New Insights From Biomarker Studies - Reyes-Leiva, David; Dols-Icardo, Oriol; Sirisi, Sonia; Cortés-Vicente, Elena; Turon-Sans, Janina; de Luna, Noemi; Blesa, Rafael; Belbin, Olivia; Montal, Victor; Alcolea, Daniel; Fortea, Juan; Lleó, Alberto; et al. (Frontiers in Neurology, 2022)
Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) lie at the ends of a clinical, genetic, and neuropathological continuum. In the last decade, it has become clear that cognitive and behavioral changes in patients with ALS are more frequent than previously recognized. Importantly, these non-motor features can impact the diagnosis, prognosis, and management of ALS. Partially overlapping neuropathological staging systems have been proposed for ALS and FTLD to describe the distribution of TAR DNA-binding protein 43 (TDP-43) aggregates outside the cortico-spinal tract. However, the relationship between TDP-43 inclusions and neurodegeneration is not well established, and other pathophysiological processes like neuroinflammation (with a prominent role of microglia), cortical hyperexcitability, and synaptic dysfunction have shown to play a central role in ALS pathophysiology. In the last decade, imaging and biofluid biomarker studies have revealed important insights into the pathophysiological underpinnings of extra-motor neurodegeneration in the ALS-FTLD continuum. Novel biomarkers tracking different aspects of ALS pathophysiology are paving the way to precision medicine approaches for the diagnosis and treatment of this disease. In this review, we aimed to summarize the clinical, genetic, and neuropathological correlates of extra-motor neurodegeneration in the ALS-FTLD continuum; and review the role of available biomarkers to characterize extra-motor neurodegeneration in ALS and their potential diagnostic and prognostic value. Recently, novel imaging biomarkers have shown significant potential to improve the diagnosis and staging of ALS. Also, biofluid biomarkers of neurodegeneration and neuroinflammation could improve the diagnostic certainty and identify patients with a faster progression rate. The use of multimodal biomarker studies integrating novel biomarkers of synaptic function and pathological aggregates of TDP-43 in-vivo show promise to unveil the pathophysiological underpinnings of extra-motor neurodegeneration in ALS. Future studies should precise the role of current and future biomarkers to advance ALS diagnostic classification and disease monitoring. These are essential steps for the design of clinical trials testing novel disease-modifying treatments.